Impairment of metabolic capacities in copper and cadmium contaminated wild yellow perch ( Perca flavescens) - Couture, Patrice; Rajender Kumar, Puja (Aquatic toxicology, 2003)
This study examined variations in resting oxygen consumption rate (ROCR), post-exercise oxygen consumption rate, relative scope for activity (RSA), liver and muscle aerobic and anaerobic capacities (using citrate synthase (CS) and lactate dehydrogenase, respectively, as indicators), and tissue biosynthetic capacities (using nucleoside diphosphate kinase (NDPK) as an indicator), in wild yellow perch from four lakes varying in copper (Cu) and cadmium (Cd) contamination. Liver Cu and Cd concentrations largely reflected environmental contamination and were positively correlated with liver protein concentrations and NDPK activities. Our results suggest that metal contamination leads to an upregulation of liver protein metabolism, presumably at least in part for the purpose of metal detoxification. In contrast, muscle NDPK activities decreased with increasing liver Cd concentrations and NDPK activities. There was a 25% decrease in ROCR for a doubling of liver Cu concentrations and a 42% decrease in RSA for a doubling of liver Cd concentrations in the range studied. Cu contamination was also associated with lower muscle CS activities. Our results support previous findings of impaired aerobic capacities in the muscle of metal-contaminated fish, and demonstrate that this impairment is also reflected in aerobic capacities of whole fish. The evidence presented suggests that mitochondria may be primary targets for inhibition by Cu, and that Cd may reduce gill respiratory capacity. Muscle aerobic and anaerobic capacities were inversely related. This work indicates that metal exposure of wild yellow perch leads to a wide range of disturbances in metabolic capacities.